Design of a Non-Circular Gear-Crank Slider Baler Mechanism Considering Slider Acceleration - WANG, Jian; WANG, Chenjie; MIAO, Long (Engineering Transactions, 2024)
A design method considering slider acceleration is proposed to reduce vibration and improve the working efficiency of a non-circular gear-crank slider baler mechanism. The ideal kinematic curves such as the displacement, velocity and acceleration curves of this proposed non-circular gear-crank slider hay baler mechanism are established. The slider strokes are divided into the working stroke and return stroke. The pitch curve of the non-circular gear is established during the slider’s working stroke based on curve smoothness characteristics and the pitch curve sealing condition. Using a compensation method, the corresponding pitch curve is constructed for the slider’s return stroke. Additionally, the design process of non-circular gear-crank slider hay baler mechanism is described in detail with special consideration given to slider acceleration. An assembly model of the non-circular gear-crank slider hay baler mechanism is created with the involute as the tooth profile. Consequently, a movement simulation is carried out using ADAMS software, and the obtained kinematic curves matched the curves established initially. The research results indicate that the proposed baler mechanism exhibits lower speed fluctuation. Additionally, the maximum power and maximum acceleration required by the proposed baler mechanism are reduced by 66.4% and by an order of magnitude, respectively, compared to an existing non-circular gear-crank slider hay baler mechanism.